Peran Moderasi Tata Kelola Perusahaan Pada Pengaruh Kompensasi CEO Terhadap Audit Fees - Zielma, Ariel; Tjaraka, Heru (Owner : Riset dan Jurnal Akuntansi, 2024)
Financial statements are instruments that represent the company's assets in a structured manner and represent an assessment of the company's performance in the current year. Auditors play an important role in protecting investors' rights by detecting misstatements or fraud in the presentation of financial statements. This study aims to examine the effect of CEO compensation on audit fees and to know that corporate governance can strengthen the effect of CEO compensation on audit fees. This study uses a quantitative approach with multiple linear analysis models and secondary data sources from the Indonesia Stock Exchange (IDX) for the 2016-2019 period. The sample used is 192 samples. The results of this study indicate that the CEO's compensation has no effect on the audit fee. This shows that the amount of the audit fee is not seen from the amount of compensation received by the CEO. In the moderating variable of corporate governance, there is no effect of CEO compensation moderated by the proportion of independent commissioners and audit committees on audit fees. This shows that the role of corporate governance does not also affect the fees given by the auditors for auditing services for their financial statements.